2019
DOI: 10.1038/s41467-019-10053-y
|View full text |Cite
|
Sign up to set email alerts
|

Decoding individual differences in STEM learning from functional MRI data

Abstract: Traditional tests of concept knowledge generate scores to assess how well a learner understands a concept. Here, we investigated whether patterns of brain activity collected during a concept knowledge task could be used to compute a neural ‘score’ to complement traditional scores of an individual’s conceptual understanding. Using a novel data-driven multivariate neuroimaging approach—informational network analysis—we successfully derived a neural score from patterns of activity across the brain that predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 38 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Much evidence suggests that the MD system can flexibly store task-relevant information in the short term (e.g., Fedorenko et al, 2013;Freedman et al, 2001;Shashidhara, Mitchell, et al, 2019;Wen et al, 2019;Woolgar et al, 2011). However, evidence from studies on processing mathematics (e.g., Amalric & Dehaene, 2019) and physics (e.g., Cetron et al, 2019;Fischer et al, 2016) further suggests that the MD system can store some domain-specific representations in the long term, perhaps for evolutionarily lateemerging and ontogenetically late-acquired domains of knowledge. Our data add to this body of evidence by showing that the MD system stores and uses information required for code comprehension.…”
Section: System's Engagement Reflects the Use Of Domain-general Rementioning
confidence: 99%
“…Much evidence suggests that the MD system can flexibly store task-relevant information in the short term (e.g., Fedorenko et al, 2013;Freedman et al, 2001;Shashidhara, Mitchell, et al, 2019;Wen et al, 2019;Woolgar et al, 2011). However, evidence from studies on processing mathematics (e.g., Amalric & Dehaene, 2019) and physics (e.g., Cetron et al, 2019;Fischer et al, 2016) further suggests that the MD system can store some domain-specific representations in the long term, perhaps for evolutionarily lateemerging and ontogenetically late-acquired domains of knowledge. Our data add to this body of evidence by showing that the MD system stores and uses information required for code comprehension.…”
Section: System's Engagement Reflects the Use Of Domain-general Rementioning
confidence: 99%
“…However, newer studies have the advantage of several additional decades of refinement of cognitive theory and methodology and are well positioned to revisit this question. For example, we can ask whether completing a specific course promotes the application of newly learned rules and strategies (Halpern, 2001), changes the way we represent a problem (Cetron et al, 2019), or improves the efficiency of domain-general cognitive processes that undergird reasoning (Guerra-Carrillo & Bunge, 2018).…”
Section: Courses That Tax Reasoning Skillsmentioning
confidence: 99%
“…Accordingly, there are many examples of how fMRI research has actually informed educational theories and practices, by providing, for example, biological explanations about brain-behaviour associations during learning and development, e.g. see recent work about the brain correlates of reading acquisition (Chyl et al, 2018; Takashima et al, 2019), and conceptual knowledge in STEM learning (Cetron et al, 2019). A review of this large body of literature can be found elsewhere (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Making inferences at the system level opens new possibilities for understanding and treating brain disorders (Thiel and Zumbansen, 2016), and in understanding brain-behaviour associations. For example, it is possible to derive useful measures or scores with task-based networks to generate individual predictions about concept knowledge in STEM learning (Cetron et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation